Production of Nanofibers Composed of CuO for the Removal of Pb(II) from Aqueous Solutions - Amábile Giotto dos Santos; Thiago Rodrigues Martins; Satheesh Krishnamurthy; Daniel Assumpção Bertuol; Eduardo Hiromitsu Tanabe (Metals)
Pollution by heavy metals such as lead is a major concern, since exposure to these metals can lead to various adverse health effects. In this work, nanofibers composed of CuO (CuONFs) were developed as a novel and promising material for Pb(II) adsorption. There have been no previous reports concerning the production of polyacrylonitrile nanofibers modified with copper sulfate pentahydrate, followed by calcination, to be utilized as a Pb(II) adsorbent. The nanofibers were obtained using the centrifugal spinning method and then were characterized before and after a calcination step using analytical techniques. Adsorption parameters were investigated, including pH, contact time, adsorbate concentration, and temperature. Satisfactory Pb (II) adsorption was reached at 298 K, pH 5.8, and a maximum adsorption of 151.34 mg g−1 was achieved, predicted by the Hill model. The kinetic data proved that Pb (II) adsorption better fitted the pseudo-second-order model, while the Hill model was confirmed to best fit the equilibrium data. Thermodynamic parameters demonstrated that the lead adsorption was favorable, spontaneous, and exothermic. The CuONFs maintained 97.51% of their initial adsorption capacity after two adsorption/desorption cycles. The results showed that CuONFs have excellent potential as an adsorbent for Pb(II), while also showing high stability during reuse.